Time-Dependent Density Functional Theory Investigation on the Electronic and Optical Properties of Poly-C,Si,Ge-acenes - Mocci, Paola (ACS Omega, 2020)
[Image: see text] We report a comparative computational investigation on the first six members of linear poly-C,Si,Ge-acenes (X(4n+2)H(2n+4), X = C,Si,Ge; n = 1, 2, 3, 4, 5, 6). We performed density functional theory (DFT) and time-dependent DFT calculations to compare morphological, electronic, and optical properties. While C-acenes are planar, Si- and Ge-acenes assume a buckled configuration. Electronic properties show similar trends as a function of size for all families. In particular, differently from C-based compounds, in the case of both Si- and Ge-acenes, the excitation energies of the strongest low-lying electronic transition (β peaks) span the visible region of the spectrum, demonstrating their size tunability. For all families, we assessed the plasmonic character of this transition and found a linear relationship for the wavelength-dependence of the β peaks as a function of the number of rings. A similar slope of about 56 nm is observed for Si- and Ge-acenes, although the peak positions of the former are located at lower wavelengths. Outcomes of this study are compared with existing theoretical results for 2D lattices and nanoribbons, and experiments where available.